Structural retrofitting in historic buildings – the case of Hearst Greek theatre, California - Bansal, Kanika (International Journal of Engineering and Technology, 2018)
A modification process after manufacturing or constructing is called Retrofitting. Within the existing built forms it refers to the transitions made to the systems in the building or the structure after it is constructed or put to its defined use. Within the present day context, there are many historic buildings that are still in use or have the potential for future use. These may not be sometimes used to their full potential, despite their historic character and environmental features as most of them do not satisfy the contemporary needs of the present day user. They may also have been built for a purpose that no longer exists or has changed and often lag behind today’s performance standards and codes. Therefore, for contemporary use of such historic buildings, Retrofitting for Rehabilitation is an opportunity for alterations and additions to suit it to the present day context. The most significant aspect of retrofitting is associated with structural refurbishment which aids for added strength, stability and safety of the historic buildings. Retrofitting measures in a historical building aims to improve the overall performance of the building, facilitate techniques to alter, repair or add to make the historic building fit for contemporary use without jeopardizing their historic qualities. Through case examples, the paper aims to bring out the trends in retrofitting and the retrofitting techniques that are being adopted in contributing to a sustainable future of historic buildings. The structural retrofitting techniques adopted at the Hearst Greek Theatre, California exemplify how historic buildings can be structurally rehabilitated to become a sustainable resource for future generations.